MULTILITERATION MODEL BASED ON ECOPEDAGOGY APPROACH IN IMPROVING ECOLOGICAL INTELLIGENCE AND DEVELOPING CHARACTERS (International Conference on Elementary Education, 2018)
Based on the assessment (conceptual-empirical) that has been done, the problem of the natural environment is crucial today to be tackled immediately. This is based on the reality of human living conditions stuck in the paradigm in the wrong development (Maldevelopment), which nature only sees as an object, mechanistic, fragmented, separated from man, so that it can easily be dominated and exploited. In other words, nature is considered a life object that is still exploited by people through the practice of pollution, destruction and various other bad actions. On this basis, an effort must be made to build a critical attitude and care in understanding different life phenomena that are harmful to the environment by repositioning human relationships with nature / the environment, the awareness of environmental ethics. and to increase ethics. On this basis, ecological education is needed to sharpen ecological sensitivity and to promote awareness of the existence of the environment as part of an ecosystem that influences human life. In line with this, efforts are needed to increase the ecological awareness of Indonesian teaching staff with ecological competence and character. These efforts must be preceded by the design of an appropriate and purposeful teaching model, one of which is based on the Ecopedagogy Approach.